Sistematización del proceso de formación, creación, montaje y circulación a partir de la obra “Cheló”; en la cátedra de danzas de la Costa Pacífica 2019-I (2021)
The objective of this work is to reconstruct the experience of the process of formation, creation and circulation of the work "Cheló" during the Danzas de la Costa Pacifica 2019-I chair. The reconstruction of this experience is supported in four categories: Training Category, which is developed in two elements, the first is the motivation that is divided into class work and pedagogical outings, supported by the theoretical and practical components, workshops and outings. carried out in the chair, the second element is the EAPEAT, an investigative element of the Bachelor's Degree in which the workshops taken with Incolballet, Univalle, Buscajá and their respective schematization are recorded. The second is the Creation Category, where elements that are worked on simultaneously within the creation and pre-production are addressed, consisting of characters, dramaturgy, music, rehearsals, dances, costumes and makeup.